Patients’ perspective about synchronous teleconsultation with a general practitioner: a mixed-method systematic literature review - Gabin F. Morillon; Marlène Guillon; Maude Laberge; Alphonse Sowanou; Thomas G. Poder (BMC Primary Care)
Abstract Background Synchronous teleconsultations using video or phone have become an increasingly popular method for delivering healthcare, especially in primary care. This modality enhances access to care, particularly for individuals in remote or underserved areas, and was especially significant during disruptions like the COVID-19 pandemic. Despite these benefits, patient perspectives on teleconsultations with general practitioners (GPs) remain underexplored. Factors such as consultation type, convenience, and technology influence patient satisfaction and acceptance, but concerns persist about the effectiveness of remote consultations for complex cases. This systematic review explores patients’ use, attitudes, experiences, satisfaction, and preferences regarding synchronous teleconsultations with GPs, aiming to identify factors influencing the choice of teleconsultation over face-to-face consultations. Methods The review included 46 studies published until March 2023, sourced from PubMed, Web of Science, EBSCO, and Cochrane Library, following PRISMA guidelines. Quantitative, qualitative, and mixed-method studies were analyzed, representing diverse contexts. Results Findings reveal that patient satisfaction with teleconsultation is influenced by consultation purpose, convenience, technological capabilities, and continuity of care. Video consultations are preferred over phone consultations, particularly for follow-ups and routine issues. Teleconsultation is seen as less effective for complex consultations requiring physical exams. Patient characteristics, including age, socioeconomic status, and technology familiarity, impact acceptance. Privacy concerns, data security, and diagnostic accuracy remain significant barriers. Continuity of care is better maintained when teleconsultation involves established patient-GP relationships. Conclusions The review emphasizes the need for hybrid care models and policies aligned with patient preferences, focusing on accessibility, technology, and privacy safeguards. Future research should address barriers for vulnerable populations and equitable access.